The equation formula of the circle is (x-h)^2 + (y-k)^2 = r^2
where (h,k) the point of the center of the circle
and (r) is the radius of the circle
so if the center of the circle = (-2,-4)
by subs. in the formula we get (x-(-2))^2 + (y-(-4))^2 = r^2
then the equation will be (x+2)^2 + (y+4)^2 = r^2
now we want to define the radius of the circle r
since point (3,8) lay on the circle so we can
then subs. in the equation to get the radius
(x+2)^2 +(y+4)^2 = r^2
(3+2)^2 +(8+4)^2 = r^2
25 + 144 = r^2
r^2 = 169
r= 13
the radius of the circle is 13
so by subs in the equation we get
(x+2)^2 + (y+4)^2 = 169
so it is the first answer in the choices
-15 - (-3) + 6
-15 - (-3) = -15 + 3 = 3 - 15 = - 12
-12 + 6 = 6 - 12 = -6
Your answer is -6
I don’t understand you buddy :/
Step-by-step explanation:
m∠1 = 180-100 = 80
m∠2 = 180-150 = 30
m∠3 = 180-(80+30) = 180 - 110 = 70
using the law of sine :
AC/sin(m∠2) = 5/sin(m∠3) ⇒ AC = sin(m∠2)*(5/sin(m∠3)) = sin(30)×(5÷sin(70))
=2.66044443119
CB/sin(m∠1) = 5/sin(m∠3) ⇒ CB = sin(m∠1)*(5/sin(m∠3)) ⇒ CB = sin(80)×(5÷sin(70)) = 5.240052604588